CPX-351 exhibits hENT-independent uptake and can be potentiated by fludarabine in leukaemic cells lines and primary refractory AML. (November 2018) - Anderson, Elizabeth; Mehta, Priyanka; Heywood, Jonathan; Rees, Barbara; Bone, Heather; Robinson, Gareth; Reynolds, Darren; Salisbury, Vyv; Mayer, Lawrence
Graphical abstract: Highlights: CPX-351 uptake is not dependant on human equilibrative nucleoside transporter 1 (hENT1) expression. Fludarabine can potentiate in vitro ara-CTP generation and cytotoxicity from CPX-351 in leukaemic cell lines. Pre-treatment of ex vivo AML blasts with fludarabine potentiates ara-CTP production from CPX-351. Abstract: CPX-351, a liposomal formulation co-encapsulating cytarabine and daunorubicin (DNR) in a synergistic 5:1 M ratio, has shown favourable response in newly diagnosed elderly high-risk AML. This study assessed intracellular ara-CTP levels following in vitro exposure of human immortalised leukaemic cell lines and primary AML blasts to CPX-351, and investigated fludarabine potentiation of intracellular ara-CTP formation from CPX-351. Comparison of intracellular handling of CPX-351 to cytarabine in HL-60 cells indicated slower conversion to ara-CTP for CPX-351, but equivalent cytotoxicity to cytarabine and combined DNR/cytarabine (DA) at 48 h, mostly likely reflecting the need for intracellular liposome processing to release encapsulated drugs. Further assessment demonstrated cytotoxicity of CPX-351 to be superior to DA at 48 and 72 h in cytarabine-resistant THP-1 cells (p < 0.001), and this effect could not be inhibited upon blockade of human equilibrative nucleoside transporter (hENT) function with dipyridamole. Assessment of Flu-CPX in primary blasts from presentation AML patients (n = 5) demonstrated a more rapid and pronounced potentiation of ara-CTP from CPX-351 than in immortalised cell lines, with 4/5 patients showing significant increases in ara-CTP, notably for those that went on to fail induction and relapse treatment in vivo (n = 3). This suggests a favourable impact on patient outcome from Flu-CPX.